Calidad de la información y nivel de satisfacción del turista sobre el área turística Irapay de la Reserva Nacional Allpahuayo Mishana. San juan. Maynas. 2023 - Silva Sandi, Jhoan Golberg (2024)
The present research work was developed in the Irapay tourist area of the Allpahuayo Mishana National Reserve. San Juan. Maynas in the year 2023, its main objective was to determine the relationship between the quality of information and the level of tourist satisfaction. The research was quantitative, prospective, relational and non experimental research design. 126 tourists participated, both national and foreign, who were present during the application of the data collection instrument. The survey technique was used and two questionnaires were applied, each with 10 questions, which had previously been validated and subjected to reliability tests. The data obtained were analyzed based on the objectives and hypotheses of the research using the statistical software SPSS, version 27 RStudio version 4.4.1. The results indicated that 80.2% of tourists considered that the information provided by the tour guides in the Allpahuayo Mishana National Reserve was of good quality. The level of tourist satisfaction, consistent with the results obtained in this work, is in line with the trends observed in other recent studies on the level of tourist satisfaction in ecotourism destinations and protected natural areas, and there is a strong and direct relationship between the quality of information and tourist satisfaction, suggesting that the perception of information quality has a considerable impact on the general satisfaction of tourists, as evidenced by various investigations in the field of tourism.